Penerapan Gamification Pada Pembelajaran Ekonomi Di SMA - Annisya'; Annisya', Annisya'; Megasari, Rizza; Satrio, Yogi Dwi; Putri, Rizky Dwi (Universitas Nusantara PGRI Kediri, 2021)
This gamification training for SMAN 3 Nganjuk teachers aims to improve teachers' understanding and skills in utilizing mobile learning in learning activities carried out especially during the pandemic era. Student learning activities are expecting not only to be carried out through the WA group or Google Classroom, but can also doing by using other applications that can attract students' learning interest. This service activity carried out in 3 stages, namely, 1) the preparation stage, 2) the implementation stage, 3) the mentoring stage using the lecture method and FGD (Focus Group Discussion). The enthusiasm of the teacher in participating in this training activity looks very big, so that the results obtained from this service are as many as 85% of the teachers have mastered the use of applications well and are ready to practice it in classroom learning.